Pengaruh Kompensasi dan Lingkungan Kerja Terhadap Loyalitas Karyawan: Studi Kasus Pada Karyawan CV. Duta Jaya Makmur - Oggi Defa Adetya; Ety Dwi Susanti (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to determine the effect of compensation and work environment on employee loyalty (case study on employees of CV. Duta Jaya Makmur). The method used in this study is quantitative with an associative approach. The population in this study was 40 people who were employees of CV. Duta Jaya Makmur. The sampling technique used the saturated sample method with all members of the population totaling 40 respondents being used as samples. The sampling technique is non-probability sampling. The data source used in the study is the primary data source obtained from employee respondents of CV. Duta Jaya Makmur, who were selected as objects and samples in the study. Data collection was carried out directly or face to face by giving questionnaires to each respondent. Data analysis used multiple linear regression analysis. The results of the hypothesis study showed that compensation and work environment simultaneously had a positive and significant effect on employee loyalty. Compensation partially had a positive and significant effect on employee loyalty. Likewise, the work environment partially had a positive and significant effect on employee loyalty.